Analýza chůze u pacientů s adolescentní idiopatickou skoliózou - Sklenský, Jan; Švehlík, Martin; Urbášek, Karel; Macková, Pavlína; Repko, Martin (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2024)
PURPOSE OF THE STUDY: The study describes changes in gait parameters (temporal-spatial parameters, kinematic parameters represented by the global Gait Deviation Index) of individuals with Adolescent Idiopathic Scoliosis (AIS) compared to the healthy population. The hypothesis assumed a difference in the observed parameters between the two mentioned groups. MATERIAL AND METHODS: In a retrospective study, the temporal-spatial parameters and Gait Deviation Index (GDI) of a cohort of 45 AIS patients (36 girls and 9 boys with the mean age of 15.2 years, the mean Cobb angle of the thoracic curve of 47.3° and the lumbar curve of 51.8°) were compared to a typically developing population of 12 healthy individuals with no musculoskeletal pathology. The difference of followed-up parameters in patients with AIS compared to normal values was assessed by one-sample Student's T-test at the significance level of p = 0.05. RESULTS: The gait analysis shows significant deviations in the gait stereotype of patients with AIS compared to the healthy population. Statistically significant differences within temporal-spatial parameters were confirmed for cadence, walking speed, step time, stride time for left leg, step length, stride length and step width. The mean GDI of the cohort reached the value of 91.07 that indicates a slight alteration of gait, however, even this change is statistically significant. DISCUSSION: In our cohort of patients with AIS, we identified a significantly reduced walking speed (on average 15.4% compared to normal values. At the same time, a reduction in cadence (by an average of 7.5%) and an increase of the stride time (by an average of 12%) were recorded. Our mean GDI values were 91.07, which is consistent with the results reported in the literature for comparable groups of AIS patients. CONCLUSIONS: Our study demonstrated that AIS significantly affects gait stereotype. The differences compared to the group of healthy individuals within temporal-spatial parameters were confirmed for cadence, walking speed, duration and length of step and stride, and step width. The kinematic analysis of gait using the global (GDI) index in patients with AIS demonstrated its slight alteration. A better understanding of the change in movement stereotypes and gait in patients with AIS can bring wider possibilities for individualizing conservative treatment and also can help prevent secondary changes in the locomotor system. KEY WORDS: adolescent idiopathic scoliosis, AIS, gait analysis, Gait Deviation Index, GDI.
Keywords: Adolescent; analýza chůze; Gait Analysis; biomechanika; lidé; retrospektivní studie; Female; mužské pohlaví; Biomechanical Phenomena; Male; skolióza; chůze (způsob); Retrospective Studies; mladiství; Gait; Scoliosis; ženské pohlaví; Humans